Spillover and spillback risks of ectoparasites by an invasive squirrel Callosciurus erythraeus in Kanto region of Japan - Hirotaka Katahira; Yuya Eguchi; Saki Hirose; Yukino Ohtani; Azusa Banzai; Yusaku Ohkubo; Tatsuki Shimamoto (International Journal for Parasitology: Parasites and Wildlife, 2022)
Invasive organisms can alter host-parasite relationships in a given ecosystem by spreading exotic parasites and/or becoming a new reservoir for native ones. Since these problems affect management programs of the invasive host organisms, it is necessary to monitor them individually. The Pallas's squirrel Callosciurus erythraeus is an invasive arboreal mammal introduced into Japan that threatens to exacerbate ecological and public health problems by spreading native and exotic parasites. However, only limited surveys have been available especially for ectoparasites, using the traditional combing method in which the possibility of oversight is inherent. Here, we evaluated the ectoparasite occurrences in Kanto region of Japan, using the whole-shaving method as an alternative approach. As a result of examining 52 hosts from two invaded districts (Yokohama and Yokosuka), chigger mites (Leptotrombidium spp.) and fleas (Ceratophyllus anisus and Ceratophyllus indages indages) were newly recovered in addition to the previously reported tick (Haemaphysalis flava) and exotic lice (Enderleinellus kumadai and Neophaematoponis callosciuri). The parasite burdens were higher in Yokosuka and in male host individuals, affecting infracommunity richness and composition. Our findings on the variety of native and exotic ectoparasites, at higher abundances in some cases than previously known, may suggest that both the spillover and spillback risks need to be adjusted upwards.